Digital Multicultural Da’wah: Content Strategy and Audience Engagement on Instagram in Contemporary Islamic Communication - Ridha Nurhaliza; Lukmnul Hakim (Islam and Social Sciences Review, 2025)
This study examines the construction and dissemination of multicultural da’wah messages on Instagram as a form of digital Islamic communication in contemporary society. Drawing on a qualitative content analysis approach, this research analyzes posts from the @nuonline_id Instagram account to explore the types, strategies, and audience responses to multicultural da’wah content. The findings reveal that multicultural da’wah is communicated through diverse themes, including interfaith harmony, local wisdom, ethnic philosophies, and religious traditions, which are strategically curated and alternated with other religious content to sustain audience engagement. The account employs inclusive narratives and culturally adaptive messaging to appeal to a heterogeneous audience within a digital environment. Furthermore, audience interaction reflected through likes, comments, and shares indicates a predominantly positive reception, suggesting that multicultural framing enhances the effectiveness of da’wah in pluralistic contexts. The study contributes to the growing literature on digital religion by demonstrating how social media platforms facilitate the transformation of traditional da’wah into interactive, audience-centered communication practices. It also highlights the role of strategic content management in promoting tolerance, inclusivity, and religious moderation in the digital public sphere. Keywords: Digital Da’wah, Multicultural Communication, Instagram, Islamic Communication, Social Media Engagement